Extracellular Vesicles From Perinatal Cells for Anti-inflammatory Therapy - Cargnoni, Anna; Papait, Andrea; Masserdotti, Alice; Pasotti, Anna; Stefani, Francesca Romana; Silini, Antonietta Rosa; Parolini, Ornella (Frontiers in Bioengineering and Biotechnology, 2021)
Perinatal cells, including cells from placenta, fetal annexes (amniotic and chorionic membranes), umbilical cord, and amniotic fluid display intrinsic immunological properties which very likely contribute to the development and growth of a semiallogeneic fetus during pregnancy. Many studies have shown that perinatal cells can inhibit the activation and modulate the functions of various inflammatory cells of the innate and adaptive immune systems, including macrophages, neutrophils, natural killer cells, dendritic cells, and T and B lymphocytes. These immunological properties, along with their easy availability and lack of ethical concerns, make perinatal cells very useful/promising in regenerative medicine. In recent years, extracellular vesicles (EVs) have gained great interest as a new therapeutic tool in regenerative medicine being a cell-free product potentially capable, thanks to the growth factors, miRNA and other bioactive molecules they convey, of modulating the inflammatory microenvironment thus favoring tissue regeneration. The immunomodulatory actions of perinatal cells have been suggested to be mediated by still not fully identified factors (secretoma) secreted either as soluble proteins/cytokines or entrapped in EVs. In this review, we will discuss how perinatal derived EVs may contribute toward the modulation of the immune response in various inflammatory pathologies (acute and chronic) by directly targeting different elements of the inflammatory microenvironment, ultimately leading to the repair and regeneration of damaged tissues.